2022
DOI: 10.3389/fcvm.2022.946289
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 9p21.3 (lncRNA and CDKN2A/2B) variant on lipid profile

Abstract: BackgroundSeveral 9p21.3 variants, such as rs1333049, rs4977574, rs10757274, rs10757278, and rs10811661, identified from recent genome-wide association studies (GWASs) are reported to be associated with coronary artery disease (CAD) susceptibility but independent of dyslipidemia. This study investigated whether these 9p21.3 variants influenced lipid profiles.Methods and resultsBy searching the PubMed and Cochrane databases, 101,099 individuals were included in the analysis. The consistent finding for the rs133… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Of note, the locus seems not to be linked to any conventional CAD risk factors, even if several variants have been reported to influence the lipid profile [ 23 ]. However, it may exert its effect through a completely novel biological mechanism related to vascular integrity and atherosclerosis development [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the locus seems not to be linked to any conventional CAD risk factors, even if several variants have been reported to influence the lipid profile [ 23 ]. However, it may exert its effect through a completely novel biological mechanism related to vascular integrity and atherosclerosis development [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the CAD risk associated with 9p21.3 genetic variants and ANRIL expression was reported being independent of traditional CAD risk factors like sex, smoking, obesity, hypertension, or diabetes [ 15 , 16 , 17 ]. However, recent studies have reported 9p21.3 risk variants having an effect on plasma lipid profile and lipid uptake in vascular cells [ 18 , 19 ]. The VITA cohort study also revealed that elevated circulating levels of ANRIL may predict later onset of T2D [ 20 ].…”
Section: Introductionmentioning
confidence: 99%